Early Caspase Activation in Leukemic Cells Subject to Etoposide-induced G2-M Arrest: Evidence of Commitment to Apoptosis Rather Than Mitotic Cell Death - SLEIMAN, Robert J; STEWART, Bernard W (Clinical cancer research, 2000)
After exposure to cytotoxic drugs at relatively low concentration, many cell types undergo G 2 -M arrest and then either mitotic cell death or, in the case of hematopoietic cells, apoptosis. We have sought to examine this phenomenon in two lymphoblastoid cell lines. After continuous or short-term exposure to etoposide (final concentration, 0.5 μ m ), up to 80% of cells accumulated at G 2 -M by 24 h, and subsequently either underwent apoptosis or re-entered the cell cycle. In this and the other studies undertaken, the CEM and MOLT-4 lines behaved similarly. Progressive accumulation of cells at G 2 -M was accompanied by increasing levels of cyclin B1. Commitment to apoptosis was assessed by evidence of caspase activation using a number of different criteria. A decreased amount of M r 32,000 procaspase-3 was evident 24–48 h after drug treatment. However, cleavage of caspase substrates poly(ADP-ribose) polymerase and lamin B indicated caspase activation occurring within 3–6 h of drug treatment. Protease activity in corresponding cell extracts increased progressively from 6 h or earlier to 24 h after the addition of etoposide to the medium. Such increase was consequent on drug treatment and not attributable to cells being at G 2 -M. Treatment with 1.5 m m caffeine abrogated etoposide-induced G 2 -M arrest, and in cells so treated, the etoposide-induced increase in protease activity was also abrogated. However, there was no impact of caffeine on cytotoxicity under these conditions. Although mitotic cell death is precipitated subsequent to prolonged G 2 -M arrest in many cell types, the present data suggest that commitment to apoptosis occurs in parallel to G 2 -M arrest in leukemic cells.